Isolation and Characterization of Bacterial Endophytes from Lycopersicon esculentum Plant and their Plant Growth Promoting Characteristics - Patel, Hardik A; Patel, Rajesh K; Khristi, Sunil M; Parikh, Kruti; Rajendran, Geetha (Nepal Journal of Biotechnology, 2012)
The study was designed to isolate and characterize bacterial endophytes from root and stem of Lycopersicon esculentum plant which was collected form different region of Gujarat. Total 18 isolates of endophytic bacteria were selected in which, all the endophytic bacteria produced one or the other different characteristics involved in plant growth promotion. They either produced phytohormones like indole acetic acid, siderophore, protease, pectinase, organic acid showed antifungal activity, chromium tolerance and solubilized phosphate. Four of the strains among the 18 showed maximum positive results of plant growth promoting regulators (PGPR) test and among them best probable isolate was selected and thus its 16SrDNA was amplified and sequenced. Only HR7 endophyte of tomato turned out to be Pseudomonas aeruginosa. It’s a gram negative coccobacili, sporeforming motile bacilli and show maximum PGPR activity. The results of our present studies indicated that above strains might be endophytic and therefore, were associated with the plant growth. Keywords: Lycopersicon esculentum; endophytic bacteria; PGPR; IAA; 16SrDNA DOI: http://dx.doi.org/10.3126/njb.v2i1.5679 Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 37-52